2016
DOI: 10.1097/inf.0000000000001225
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Febrile Infants With Enterococcal and Gram-negative Urinary Tract Infections

Abstract: Febrile infants with enterococcal UTIs had a low likelihood of adverse events or severe clinical course, similar to those with Gram-negative UTIs. Infants with enterococcal UTIs frequently had underlying hydronephrosis and/or vesicoureteral reflux. The preliminary diagnosis of enterococcal UTIs may be inaccurate if based on UA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
(32 reference statements)
2
5
0
Order By: Relevance
“…15 Previous studies have demonstrated the significant differences between Enterococcus and gram-negative pathogens in febrile infants, including differences in gestational age, resistance patterns, pyuria, and urinary tract abnormalities. 6,14,16,17 Our findings of variation in LOS compared with gram-negative pathogens substantiates previous findings differences in clinical course of Enterococcus UTIs. 16…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…15 Previous studies have demonstrated the significant differences between Enterococcus and gram-negative pathogens in febrile infants, including differences in gestational age, resistance patterns, pyuria, and urinary tract abnormalities. 6,14,16,17 Our findings of variation in LOS compared with gram-negative pathogens substantiates previous findings differences in clinical course of Enterococcus UTIs. 16…”
Section: Discussionsupporting
confidence: 91%
“…6,14,16,17 Our findings of variation in LOS compared with gram-negative pathogens substantiates previous findings differences in clinical course of Enterococcus UTIs. 16…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, though most UTIs caused by E. coli demonstrate an inflammatory response (and positive UA), several studies in children have found that certain non-E. coli uropathogens and gram-positive organisms are less likely to be associated with pyuria. 3436 uNGAL may offer an advantage in this respect as NGAL levels in UTIs appear to mainly reflect the kidneys’ response to inflammation, independent of leukocyte activation. 11,25…”
Section: Discussionmentioning
confidence: 99%
“…Lubell et al in a multicenter emergency department study of 1870 infants 29–60 days of age diagnosed with UTI based on symptoms and either pyuria or a positive urine gram stain found that 6% had colony counts of 10,000–49,000 CFU/mL, 3% reported as 10,000 to 100,000 CFU/ml, and 20% reported as 50,000 to 100,000 CFU/ml. 13 Thus potentially 9% of these infants might not have been diagnosed with a UTI unless the colony count cut-off is decreased to 10,000 CFU/ml. Similarly Schroeder et al report that 5% of their infants less than 3 months of age with a bacteremic UTI had colony counts between 10,000 and 49,000 CFU/ml.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Lubell found that the sensitivity of pyuria was 75.9% for infants with an enterocoocal UTI compared with 93.9% for those with an E. coli UTI. 13 Perhaps when organisms other than E coli are found in a urine without pyuria, physicians should have a higher index of suspicion for a UTI as these organisms may generate less of an inflammatory response.…”
Section: Discussionmentioning
confidence: 99%